2020
DOI: 10.4103/jispcd.jispcd_177_20
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial efficacy of calcium hydroxide with iodoform versus calcium hydroxide with camphorated paramonochlorophenol as intrachannel pastes on an Enterococcus faecalis biofilm: A comparative in vitro study

Abstract: A BSTRACT Objective: The objective of this study was to assess in vitro the antibacterial efficacy of Ca(OH) 2 with iodoform versus Ca(OH) 2 with camphorated paramonochlorophenol as intrachannel pastes on an Enterococcus faecalis biofilm. Materials and Methods: The diffusion method was used in wells. The strain used was E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…In the pulp and connective tissue of the tooth, this action is stimulated due to the occurrence of mineralization through alkaline phosphatase and fibronectin 12 . When associated with IM, according to Jara et al 22 , this action serves to control the infection by reducing necessary nutrients and preventing the continuation of bacterial proliferation, forming a physical-chemical barrier. In the case discussed in this report, the material was recommended due to the characteristics mentioned above, aiming to treat the periapical lesion in the periapex.…”
Section: Discussionmentioning
confidence: 99%
“…In the pulp and connective tissue of the tooth, this action is stimulated due to the occurrence of mineralization through alkaline phosphatase and fibronectin 12 . When associated with IM, according to Jara et al 22 , this action serves to control the infection by reducing necessary nutrients and preventing the continuation of bacterial proliferation, forming a physical-chemical barrier. In the case discussed in this report, the material was recommended due to the characteristics mentioned above, aiming to treat the periapical lesion in the periapex.…”
Section: Discussionmentioning
confidence: 99%
“…According to Zacharczuk (2019) and Najjar (2019), this association provides an alkaline paste, with antimicrobial potential, biocompatibility, increased radiopacity of the material, in view of the deficiency of calcium hydroxide at this point and simplification during application in the conduits. On the other hand, some studies have not shown effective antimicrobial action, being inferior to other filling pastes (JARA et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Йодоформ -антисептичний засіб, який широко використовується місцево в хірургічній стоматології і в ендодонтії [4,9]. Впливу йодоформу у складі комплексних стоматологічних матеріалів і препаратів на мікроорганізми присвятила увагу значна кількість дослідників [13,14]. Результати, які вони отримали, суттєво різнились.…”
unclassified